Les migrations quotidiennes de travail des actifs de la Petite Bourgogne - Brunet, Yves (Université de Montréal, 1971)
Keywords: Petite-Bourgogne; Quartiers

Le programme de rénovation de la Petite Bourgogne, 1965-1968: analyse décisionnelle - Bougie, André (Université de Montréal, 1971)
Keywords: Petite-Bourgogne; Quartiers

Typologies comparées des travailleurs de la Petite Bourgogne (Montréal): Une analyse factorielle des migrations alternantes - Brunet, Yves (Revue de Géographie de Montréal, 1972)
Number: 3
Keywords: Petite-Bourgogne; Quartiers

L'idéologie du réaménagement urbain à Québec (quartier Saint-Roch) et à Montréal (quartier Petite Bourgogne) - Mayer, Robert (Université Laval, 1976)
Keywords: Petite-Bourgogne; Quartiers

La rénovation urbaine et le phénomène de pression: étude monographique, le cas de "la petite Bourgogne" à Montréal - Piotte, Serge Y. (Université de Montréal, 1970)
Keywords: Petite-Bourgogne; Quartiers

Sur les pas d’Oscar et d’Oliver dans la Petite-Bourgogne. Première partie : Vie associative dans le quartier - Willis, John (Cap-aux-Diamants, 2023)
issued: 2023-22-00
Keywords: Petite-Bourgogne; Quartiers

Les migrations alternantes: le cas de la Petite Bourgogne. L'influence des caractéristiques socio-économiques sur le comportement migratoire de la main-d'oeuvre - Brunet, Yves (Revue de Géographie de Montréal, 1971)
Number: 3
Keywords: Petite-Bourgogne; Quartiers

Participation citoyenne et cohésion sociale : le cas du quartier de la Petite-Bourgogne à Montréal - Desforges, Virginie (Université du Québec à Montréal, 2017)
Keywords: Groupes populaires; Petite-Bourgogne; Quartiers

Enjeux de redéveloppement et morphologie urbaine aux abords du canal de Lachine: Petite-Bourgogne et Pointe-Sainte-Charles - Gildas, Michel (Institut national de la recherche scientifique - Urbanisation, Culture et Société, 2000)
Keywords: Lachine (canal); Petite-Bourgogne; Pointe-Saint-Charles; Quartiers

Political Power and Urban Redevelopment: A Case Study of Montreal - Kardos, Robert (Université McGill, 1969)
Keywords: Logement; Petite-Bourgogne

Les prix d'excellence 1994 - Les habitations Georges-Vanier, Montréal (ARQ - Architecture Québec, 1994)
Keywords: Petite-Bourgogne; Quartiers

Mixité sociale et prise en charge citoyenne : le cas de l'Équipe mobile en alimentation - Fortin, Jany (Université du Québec à Montréal, 2017)
Keywords: Alimentation; Petite-Bourgogne; Quartiers

"Un petit pouvoir": The Compagnie des jeunes Canadiens, Animation Sociale, and Citizens’ Committees in Little Burgundy, Montreal, 1967-74 - Langford, Will (The Global Politics of Poverty in Canada. Development Programs and Democracy, 1964-1979, 2021)
Keywords: Groupes populaires; Pauvreté; Petite-Bourgogne; Quartiers

Little Burgundy: The Interwoven Histories of Race, Residence, and Work in Twentieth-Century Montreal - High, Steven (Urban History Review / Revue d'histoire urbaine, 2017)
issued: 2017-23-00
Keywords: Chemins de fer; Noirs; Petite-Bourgogne; Quartiers; Travail

Urban governance after urban renewal: The legacies of renewal and the logics of neighbourhood action in post-renewal Little Burgundy (1979 – 1995) - Goyette, Kiley (Université Concordia, 2017)
Keywords: Gentrification; Groupes populaires; Logement; Petite-Bourgogne; Quartiers

Deindustrializing Montreal: Entangled Histories of Race, Residence, and Class - High, Steven C (McGill-Queen's University Press, 2022)
"Point Saint-Charles, a historically white working-class neighbourhood with a strong Irish and French presence, and Little Burgundy, a multiracial neighbourhood that is home to the city's English-speaking Black community, face each other across Montreal's Lachine Canal, once an artery around which work and industry in Montreal were clustered and by which these two communities were formed and divided. Deindustrializing Montreal challenges the deepening divergence of class and race analysis by recognizing the intimate relationship between capitalism, class struggles, and racial inequality. Fundamentally, deindustrialization is a process of physical and social ruination as well as part of a wider political project that leaves working-class communities impoverished and demoralized. The structural violence of capitalism occurs gradually and out of sight, but it doesn't play out the same for everyone. Point Saint-Charles was left to rot until it was revalorized by gentrification, whereas Little Burgundy was torn apart by urban renewal and highway construction. This historical divergence had profound consequences in how urban change has been experienced, understood, and remembered. Drawing extensive interviews, a massive and varied archive of imagery, and original photography by David Lewis into a complex chorus, Steven High brings these communities to life, tracing their history from their earliest years to their decline and their current reality. He extends the analysis of deindustrialization, often focused on single-industry towns, to cities that have seemingly made the post-industrial transition. The urban neighbourhood has never been a settled concept, and its apparent innocence masks considerable contestation, divergence, and change over time. Deindustrializing Montreal thinks critically about locality, revealing how heritage becomes an agent of gentrification, investigating how places like Little Burgundy and the Point acquire race and class identities, and questioning what is preserved and for whom."–
Keywords: Gentrification; Irlandais; Lachine (canal); Noirs; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Travail

À l'affiche dans le Sud-Ouest... - Labrosse, Richard; Racine, Yolande (Éditions Histoire Québec, 2013)
Keywords: Cinéma; Côte-Saint-Paul; Griffintown; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Saint-Henri; Sainte-Cunégonde; Ville Émard

La Petite-Bourgone: bercail de l'industrie et quartier historique multiracial de Montréal - High, Steven (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Anglophones; Canadien National; Francophones; Grand Tronc; Lachine (canal); Montreal Rolling Mills; Noirs; Petite-Bourgogne; Quartiers; Sainte-Cunégonde

L'axe du canal de Lachine et les quartiers du Sud-Ouest. Grandeur et misère du berceau de l'industrialisation du pays? - Poitras, Claire (Montréal : la cité des cités, 2017)
Keywords: Arrondissements; Côte-Saint-Paul; Griffintown; Groupes populaires; Lachine (canal); Le Sud-Ouest (arrondissement); Patrimoine; Petite-Bourgogne; Pointe-Saint-Charles; Quartiers; Saint-Henri; Ville Émard